2011
DOI: 10.1111/j.1525-1594.2011.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposome‐Encapsulated Hemoglobin Alleviates Hearing Loss After Transient Cochlear Ischemia and Reperfusion in the Gerbil

Abstract: To test liposome-encapsulated hemoglobin (LEH) in transient cochlear ischemia/reperfusion as a model of sudden deafness, Mongolian gerbils were randomly assigned to receive 2 mL/kg of either low-affinity LEH (l-LEH, P₅₀0₂ = 40 mm Hg), high-affinity LEH (h-LEH, P₅₀0₂ = 10 mm Hg), homologous red blood cells (RBCs), or saline (each group n = 6) 30 min before 15-min occlusion of the bilateral vertebral arteries and reperfusion. Sequential changes in hearing were assessed by auditory brain response 1, 4, and 7 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 25 publications
3
39
0
Order By: Relevance
“…These observations of whole‐brain I/R showed that l ‐LEH was protective in SAT performance and amygdala morphology but not in the Morris water maze task and CA1 cellularity in the hippocampus. Although these observations may appear contradictory, they might be compatible with our previous observations on focal brain ischemia, where LEH was protective largely in the cortex but not as much in the basal ganglia . Such observation may also be compatible with the results of Hamadate , who demonstrated the benefits of l ‐LEH treatment in a four‐vessel occlusion model in the rat.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These observations of whole‐brain I/R showed that l ‐LEH was protective in SAT performance and amygdala morphology but not in the Morris water maze task and CA1 cellularity in the hippocampus. Although these observations may appear contradictory, they might be compatible with our previous observations on focal brain ischemia, where LEH was protective largely in the cortex but not as much in the basal ganglia . Such observation may also be compatible with the results of Hamadate , who demonstrated the benefits of l ‐LEH treatment in a four‐vessel occlusion model in the rat.…”
Section: Discussionsupporting
confidence: 90%
“…Benefits of LEH in focal brain ischemia were mainly in the cortex and amygdala but not so much in the basal ganglia and hippocampus, suggesting possible difference(s) in perfusion patterns during ischemia and oxidative stress at reperfusion. In the current study, we examined the effect(s) of l ‐LEH on global and complete brain ischemia, as there could be differences from focal ischemia with regard to the role of collaterals and the severity of reperfusion injury.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, h ‐LEH has been reported to be more efficient, equally benefiting with 1/5 to 1/25 dosage, than l ‐LEH in cerebral ischemia/reperfusion . Similar results are observed in cochlear ischemia/reperfusion , where it is more protective of hearing in the order of h ‐LEH, l ‐LEH, and saline or RBC. Thus, both the particle size and O 2 ‐affinity appear to be involved in O 2 delivery and aerobic metabolism.…”
Section: Discussionmentioning
confidence: 57%
“…It has been our consistent observation that liposome‐encapsulated hemoglobin (LEH), specifically with high O 2 affinity ( h ‐LEH, P 50 O 2 = 8–17 mm Hg), has been associated with suppressed inflammation to promote wound healing , reduce damage after ischemia/reperfusion , and enhance antitumor therapies . Whereas LEH with low O 2 affinity ( l ‐LEH, P 50 O 2 = 40–50 mm Hg) was able to maintain O 2 delivery as a whole in rabbits under hemorrhagic shock, it was not associated with improved peripheral perfusion or extended survival .…”
mentioning
confidence: 95%